2014
DOI: 10.1073/pnas.1408821111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic–epigenetic dysregulation of thymic TSH receptor gene expression triggers thyroid autoimmunity

Abstract: Significance Graves disease (GD) is an autoimmune disease caused by interactions between genetic, epigenetic, and environmental factors. The thyrotropin receptor ( TSHR ) is the major autoantigen in GD and is a key GD susceptibility gene. SNPs in intron 1 of the TSHR are associated with GD, but the causative variant and the mechanisms are unknown. By mapping epigenetic modifications induced by IFNα, a viral-induced cytokine triggering GD, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 37 publications
3
64
0
1
Order By: Relevance
“…Additionally, we also demonstrated that the thyroid transcription factor 1 TTF1 (also known as NK2 homeobox 1, NKX2-1), which activates TSHR transcription in the thyroid gland [106], was not expressed in the thymus. This finding supported the concept that regulation of tissue-restricted antigens gene expression in the thymus is controlled by different mechanisms than in the primary tissue.…”
Section: Reviewmentioning
confidence: 77%
“…Additionally, we also demonstrated that the thyroid transcription factor 1 TTF1 (also known as NK2 homeobox 1, NKX2-1), which activates TSHR transcription in the thyroid gland [106], was not expressed in the thymus. This finding supported the concept that regulation of tissue-restricted antigens gene expression in the thymus is controlled by different mechanisms than in the primary tissue.…”
Section: Reviewmentioning
confidence: 77%
“…86 Accordingly, deregulation of TSHR-mediated regulatory activity of gene expression, through the inhibition of its transcriptional repressor promyelocytic leukemia zinc finger protein in the thymus, triggers thyroid auto immunity due to the escape of TSHR-reactive T cells from negative selection. 87 Additionally, TRH, which encodes prothyrotropin-releasing hormone, is also transcribed in the thymus of the rat. 88 Given the local production of prothyrotropin-releasing hormone, the intrathymic expression of the thyrotropin receptor and the fact that this neuropeptide is able to enhance thymocyte proliferation, 89,90 an autocrine/paracrine circuit mediated by thyrotropin receptor might control the thymus physiology.…”
Section: Leptinmentioning
confidence: 99%
“…The absence of HCV clearance from thyrocytes perpetuates the chronic inflammation and autoimmunity. a-IFN triggers AITD through an epigenetic mechanism involving variant of Tg and TSHr gene promoter [101,102] . Moreover, a-IFN locally enhances the expression of TSH-r, Tg, TPO and HLA class Ⅰ molecules on thyrocytes and the secretion of the potent proinflammatory IL-2 cytokine [11] .…”
Section: Development Of Aitd During the A-ifn Treatment For Hcv Chronmentioning
confidence: 99%